Modulating crystallization behavior and functional properties of diacylglycerol-based margarines through chilling temperature control - Ke, Wanting; Liang, Xinzhe; Lee, Yee Ying; Tan, Chin Ping; Pei, Hong Shyang; Wang, Yong; Zhang, Zhen (Elsevier, 2026)
Diacylglycerol (DAG)-enriched margarines offer significant health advantages over traditional triacylglycerol (TAG) counterparts but require precise crystallization control to achieve desired textures. This study systematically quantified how chilling temperature (−10 °C to 10 °C) modulates the crystallization network, rheology, and functional performance of palm oil (PO)-DAG margarines (70:30 w/w). Results revealed that lower temperatures (−10 °C) enhanced nucleation rates, yielding denser crystalline scaffolds dominated by β-polymorphs (52.11%), higher solid fat content, and an elevated storage modulus (G′ > 105 Pa). Conversely, higher temperatures (10 °C) promoted β'-polymorphs (77.09%), smaller crystal sizes, and reduced hydrogen bonding. These crystallization characteristics collectively indicate that 0 °C is the optimal chilling temperature, as it increases β'-polymorphic content and promotes the formation of fine needle-like crystals (Df > 1.90) within a uniform network structure. Functionally, samples quenched at 0 °C achieved superior whipping performance, reducing specific gravity compared to 10 °C counterparts due to improved air incorporation while concurrently, maintaining competitive storage stability. This study establishes chilling temperature as a critical lever for tailoring health-oriented margarines providing the food industry with a scientific basis and precise processing parameter to manufacture next-generation margarines that deliver enhanced health benefits, superior texture, and improved functionality.